2019
DOI: 10.1093/cid/ciy1132
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir Monotherapy Versus Dolutegravir/Abacavir/Lamivudine for Virologically Suppressed People Living With Chronic Human Immunodeficiency Virus Infection: The Randomized Noninferiority MONotherapy of TiviCAY Trial

Abstract: Background We investigated whether dolutegravir (DTG) monotherapy could be used to maintain virological suppression in people living with human immunodeficiency virus (HIV) on a successful dolutegravir-based triple therapy. Methods MONCAY (MONotherapy of TiviCAY) was a 48-week, multicentric, randomized, open-label, 12% noninferiority margin trial. Patients with CD4 nadir >100/μL, plasma HIV-1 RNA <50 copies/mL for ≥12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…When including this variable, the tau-squared were reduced from 1.17 (95% CI 0.33-2.19) to 0.00 (95% CI 0.00-1.11) in the 24 week analysis and from 1.37 (95% CI 0.54-2.15) to 0.00 (95% CI 0.00-1.00) in the 48 week analysis. The inclusion of other variables did not impact the estimates of tau-squared.” Discussion: (page 9) Please provide some references (at least one) for the impact of M184V on viral fitness (this one is of interest for DTG-based regimen: doi: 10.1097/QAD.0000000000001191)(page 9) I think authors should provide some data on VF (%, emerging mutations) during switch from a triple therapy to another one (in order to have an “historical comparator” for dual therapy)(page 10, “In addition, more data on the activity of DTG-based simplified regimens in compartments other than blood are needed.”) There are some references for mono- or dual-therapy in the genital tract (Hocqueloux et al 1 and Gianella et al 2 )and CNS (Doco Lecompte et al 3 )(page 10) Authors should cite recent reports (all communicated at the IAS 2018 in Amsterdam) confirming their conclusions, even though they cannot include them in the analyses: two randomized-controlled clinical trials on DTG monotherapy (Braun et al 4  and Hocqueloux et al 5 ), the extended follow-up of the SWORD trials at week 100 (Aboud et al 6 ) and results of the GEMINI trials (Cahn et al 7  ). References: (references 25 and 28) I think two references (Gantner and Bonijoly) are duplicates (as they are based on the analyze of the same database; Bonijoly et al have included more patients / with longer duration of follow-up than Gantner). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When including this variable, the tau-squared were reduced from 1.17 (95% CI 0.33-2.19) to 0.00 (95% CI 0.00-1.11) in the 24 week analysis and from 1.37 (95% CI 0.54-2.15) to 0.00 (95% CI 0.00-1.00) in the 48 week analysis. The inclusion of other variables did not impact the estimates of tau-squared.” Discussion: (page 9) Please provide some references (at least one) for the impact of M184V on viral fitness (this one is of interest for DTG-based regimen: doi: 10.1097/QAD.0000000000001191)(page 9) I think authors should provide some data on VF (%, emerging mutations) during switch from a triple therapy to another one (in order to have an “historical comparator” for dual therapy)(page 10, “In addition, more data on the activity of DTG-based simplified regimens in compartments other than blood are needed.”) There are some references for mono- or dual-therapy in the genital tract (Hocqueloux et al 1 and Gianella et al 2 )and CNS (Doco Lecompte et al 3 )(page 10) Authors should cite recent reports (all communicated at the IAS 2018 in Amsterdam) confirming their conclusions, even though they cannot include them in the analyses: two randomized-controlled clinical trials on DTG monotherapy (Braun et al 4  and Hocqueloux et al 5 ), the extended follow-up of the SWORD trials at week 100 (Aboud et al 6 ) and results of the GEMINI trials (Cahn et al 7  ). References: (references 25 and 28) I think two references (Gantner and Bonijoly) are duplicates (as they are based on the analyze of the same database; Bonijoly et al have included more patients / with longer duration of follow-up than Gantner). …”
mentioning
confidence: 99%
“…(page 10) Authors should cite recent reports (all communicated at the IAS 2018 in Amsterdam) confirming their conclusions, even though they cannot include them in the analyses: two randomized-controlled clinical trials on DTG monotherapy (Braun et al 4  and Hocqueloux et al 5 ), the extended follow-up of the SWORD trials at week 100 (Aboud et al 6 ) and results of the GEMINI trials (Cahn et al 7  ).…”
mentioning
confidence: 99%
“…Dolutegravir þ 3TC demonstrated non-inferiority in the GEMINI-1 and GEMINI-2 trials compared to three drugs (dolutegravir þ TDF/FTC) after 48 weeks of treatment of previously untreated patients without detectable drug resistance [41]. Previous studies have shown a high risk of development of resistance to INSTI in dolutegravir monotherapy [42,43], which is why it is of great importance that dolutegravir þ 3TC is given to patients with no known prior virological failure or history of 3TC resistance. The working group's assessment is that dolutegravir þ 3TC is a conceivable new strategy, especially when switching in patients with already suppressed virus, but that this combination should be given with great caution until results from longer follow-up studies are available.…”
Section: Combinations With Only Two Active Drugsmentioning
confidence: 99%
“…In an openlabel, phase 2, randomized non-inferiority trial, DTG monotherapy was non-inferior to combination ART at 24 weeks; however, viriologic failure was seen after 24 weeks with continued monotherapy, which led to DTG resistance [6]. The switch to certain monotherapy treatments occurred in patients already virologically suppressed; these regimens have largely failed to maintain viral suppression for an extended duration, with frequent cases of virologic rebound and emerging resistance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%